Utility of Supine Lateral Radiographs for Assessment of Lumbar Segmental Instability in Degenerative Lumbar Spondylolisthesis. Issue 18 (15th September 2018) - Tarpada, Sandip P.; Cho, Woojin; Chen, Foster; Amorosa, Louis F.
Abstract : Study Design: Retrospective chart review Objective: To determine whether supine lateral radiographs increase the amount of segmental instability visualized in single-level lumbar degenerative spondylolisthesis, when compared to traditional lateral flexion-extension radiographs. We hypothesized that supine radiographs increase the amount of segmental instability seen in single-level lumbar spondylolisthesis when compared to flexion-extension. Summary of Background Data: Accurate evaluation of segmental instability is critical to the management of lumbar spondylolisthesis. Standing flexion-extension lateral radiographs are routinely obtained, as it is believed to precipitate the forward-backward motion of the segment; however, recent studies with magnetic resonance imaging and computed tomography have shown that the relaxed supine position can facilitate the reduction of the anterolisthesed segment. Here, we show that inclusion of supine lateral radiographs increases the amount of segmental instability seen in single-level lumbar spondylolisthesis when compared to traditional lateral radiographs. Methods: Supine lateral radiographs were added to the routine evaluation (standing neutral/flexion/extension lateral radiographs) of symptomatic degenerative spondylolisthesis at our institution. In this retrospective study, 59 patients were included. The amount of listhesis was measured and compared on each radiograph: standing neutral lateral ("neutral"), standing flexion lateral ("flexion"), standing extension lateral ("extension"), and supine lateral ("supine"). Results: A total of 59 patients (51 women, 8 men), with a mean age of 63.0 years (±9.85 yr) were included. The mean mobility seen with flexion-extension was 5.53 ± 4.11. The mean mobility seen with flexion-supine was 7.83% ± 4.67%. This difference was significant in paired t test ( P  = 0.00133), and independent of age and body mass index. Maximal mobility was seen between flexion and supine radiographs in 37 patients, between neutral and supine radiographs in 11 cases, and between traditional flexion-extension studies in 11 cases. Conclusion: Supine radiograph demonstrates more reduction in anterolisthesis than the extension radiograph. Incorporation of a supine lateral radiograph in place of extension radiograph can improve our understanding of segmental mobility when evaluating degenerative spondylolisthesis. Level of Evidence: 3